AKSIOLOGI PEMBELAJARAN S}ARAF DALAM MEMBACA KITAB KUNING - Ahmad R.; Hastang Hastang (Didaktika : Jurnal Kependidikan, 2020)
This research aims to find out how the application of S}araf in reading yellow book using qualitative descriptive research. The subjects of the study were lecturers of science s}araf, lecturers of Qiraah and Mut}alaáh as well as students of  Arabic program at IAIN Bone. Data were collected through observation, interview and documentation techniques. Data analysis was carried out in three stages continuously including data reduction, data display and conclusion/verification withdrawal stage. The results shows that S}araf learning materials are divided into three stages; S}araf 1, S}araf2 and S}araf 3 by using various methods, including lecturing, discussions, demontation of bags }rif and tadrib. Tadrib/exercise was carried out with bag exercise }rif, practicing to make sentences, analyzing the function and form of words and giving harakat to a reading.  The application of s}araf in reading the yellow book was began by giving harakat to a text to determine its meaning. S}araf, that has a study on the formation of the word is very instrumental in this case. Mastery of the bag will make it easier to read a reading, whether it has harakat or not. The understanding of an Arabic text is not limited to the mastery of any existing mufradat, but rather must pay attention to the form of the word used.